Checklist of sergestid shrimps, Acetes (Decapoda: Sergestidae) from selected sites along the coastal water of Sarawak, Malaysia - Muhammad Nur Arif Othman; Ruhana Hassan; Chen, Cheng Ann (Malaysian Nature Society, 2020)
Acetes is exploited by the local people of Sarawak as a source of income during its bloom season, processed into local products such as fermented shrimp paste and pickle. Despite its importance in socio-economy, little is known on Acetes species composition in the coastal water of Sarawak, Malaysia. The objective of this study is to provide checklist of Acetes species found in the coastal water of Sarawak. Acetes samples were collected at three different sites namely Lundu, Telaga Air and Miri using bottom trawl net and traditional fishing gears. Four species were identified based on the morphological characters namely A. erythraeus, A. serrulatus, A. japonicus and A. indicus and A. erythraeus is the new record for Sarawak. © 2020 Malaysian Nature Society. All rights reserved.